Epithelial Fluid Transport is Due to Electro-osmosis (80%), Plus Osmosis (20%) - Fischbarg, Jorge (J Membr Biol, 2017)
Epithelial fluid transport, an important physiological process shrouded in a long-standing enigma, may finally be moving closer to a solution. We propose that, for the corneal endothelium, relative proportions for the driving forces for fluid transport are 80% of paracellular electro-osmosis, and 20% classical transcellular osmosis. These operate in a cyclical process with a period of 9.2 s, which is dictated by the decrease and exhaustion of cellular Na(+). Paracellular electro-osmosis is sketched here, and partially discussed as much as the subject still allows; transcellular osmosis is presented at length.